Cervical fluid interleukin 6 and intra-amniotic complications of preterm prelabor rupture of membranes. (3rd April 2018) - Musilova, Ivana; Andrys, Ctirad; Drahosova, Marcela; Soucek, Ondrej; Pliskova, Lenka; Jacobsson, Bo; Kacerovsky, Marian
Abstract: Objective: To determine if cervical fluid interleukin (IL)-6 concentrations in women with preterm prelabor rupture of membranes (PPROM) allows identification of microbial invasion of the amniotic cavity (MIAC) and/or intra-amniotic inflammation (IAI). Methods: One hundred forty-four women with singleton pregnancies complicated by PPROM were included in this prospective cohort study. Cervical and amniotic fluids were collected at the time of admission and concentrations of IL-6 were measured using an ELISA and point-of-care test, respectively. Cervical fluid was obtained using a Dacron polyester swab and amniotic fluid was obtained by transabdominal amniocentesis. MIAC was diagnosed based on a positive PCR result for Ureaplasma species, M. hominis, and/or C. trachomatis and/or by positivity for the 16 S rRNA gene. IAI was defined as amniotic fluid point-of-care IL-6 concentrations ≥745 pg/mL. The women were assigned to four subgroups based on the presence of MIAC and/or IAI: microbial-associated IAI (both MIAC and IAI), sterile IAI (IAI alone), MIAC alone, and without either MIAC or IAI. Results: (1) Women with microbial-associated IAI had higher cervical fluid IL-6 concentrations (median 560 pg/mL) than did women with sterile IAI (median 303 pg/mL; p = .001), women with MIAC alone (median 135 pg/mL; p = .0004), and women without MIAC and IAI (median 180 pg/mL; p = .0001). (2) No differences were found in cervical fluid IL-6 concentrations among women with sterile IAI, with MIAC alone, and without MIAC and IAI. (3) A positive correlation was observed between cervical fluid IL-6 concentrations and the amount of Ureaplasma species in amniotic fluid (copies DNA/mL; rho = 0.57, p < .0001). (4) A weak positive correlation was detected between cervical and amniotic fluid IL-6 concentrations (rho = 0.33, p < .0001). Conclusions: The presence of microbial-associated IAI is associated with the highest cervical fluid IL-6 concentrations. Cervical IL-6 can be helpful in the identification of microbial-associated IAI.